2003
DOI: 10.1016/s0269-7491(02)00479-7
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis and stage specific toxicity induced by cadmium in an insect model, the queen blowfly, Phormia regina Meig.

Abstract: Hormesis is an adaptive response, commonly characterized by a biphasic doseresponse that can be either directly induced, or the result of compensatory biological processes following an initial disruption in homeostasis [Calabrese and Baldwin, Hum. Exp. Toxicol., 21 (2002), 91]. Low and environmentally relevant levels of dietary cadmium significantly enhanced the pupation rate of blowfly larvae, while higher doses inhibited pupation success. However, dietary cadmium at all exposure levels adversely affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 16 publications
5
37
2
Order By: Relevance
“…Similarly, marine amphipods exhibited increased growth and reproduction when exposed to relatively low doses of copper (Correia et al, 2001). At similar concentrations to the ones in the present study, sea scallops also exhibited a mild hormetic effect of cadmium on gamete maturation (Gould et al, 1989), and cadmiumexposed blowfly larvae display a hormetic-like biphasic response for pupation success (Nascarella et al, 2003). Finally, the cyanobacteria Spirulina platensis displays increased growth when exposed to low levels of nickel (Azeez and Banerjee, 1991).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly, marine amphipods exhibited increased growth and reproduction when exposed to relatively low doses of copper (Correia et al, 2001). At similar concentrations to the ones in the present study, sea scallops also exhibited a mild hormetic effect of cadmium on gamete maturation (Gould et al, 1989), and cadmiumexposed blowfly larvae display a hormetic-like biphasic response for pupation success (Nascarella et al, 2003). Finally, the cyanobacteria Spirulina platensis displays increased growth when exposed to low levels of nickel (Azeez and Banerjee, 1991).…”
Section: Discussionsupporting
confidence: 75%
“…In an extensive review of 4000 toxicological studies, Calabrese and Baldwin (1997 found that 350 of the studies revealed evidence of hormesis. They looked at a broad group of taxa, from bacteria to mammals, exposed to inorganics (Nascarella et al, 2003), organics (Laughlin et al, 1981;Zanuncio et al, 2003), heat (Hercus et al, 2003), and gamma radiation (Pollycove and Feinendegen, 2001). In order of frequency observed, hormetic effects were increase in growth, longevity (Cypser and Johnson, 2002;Rattan, 2001), reproduction, survival, and also metabolic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Calabrese and Baldwin, 2001;Nascarella et al, 2003;Calabrese and Blain, 2005;Lefcort et al, 2008). If the same hormetic response was present, we would expect that the higher concentration presented higher toxicity values (higher IBR values) and the lower concentration lower toxicity values than our control, which is not the case.…”
Section: Discussionmentioning
confidence: 77%
“…Whether higher Cd doses combined with hypoxia would have resulted in stimulation of proton leak beyond that caused by hypoxia alone remains unknown. Nonetheless, the biphasic response observed in the present study is akin to hormesis (Calabrese and Baldwin, 2002;Calabrese and Baldwin, 2003;Nascarella et al, 2003), wherein low doses of stereotypically noxious (inhibitory) substances elicit beneficial (stimulatory) effects. A similar beneficial response was observed with regards to the combined action on complex I activity in that while hypoxia acting alone inhibited complex I activity, administration of 5 μmol l −1 Cd partially reversed this inhibition.…”
Section: Research Articlementioning
confidence: 73%